THE ORCHID GENUS LUISIA IN INDONESIA - DIAH SULISTIARINI (BRIN Publishing (Penerbit BRIN), 1988)
Nine species and one new variety of the genus Luisia are recognized in Indonesia. The newly proposed variety is L. zollingeri Rchb. f. var. iati-petala ( J. J. S. ) Sulistiarini. Complete descriptions, key to all species based on morphological characters as well as lists of specimens examined are presented.